1997
DOI: 10.1007/bf01987485
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between paper and adsorbed molecules

Abstract: We have studied the geometry and energy involved in the interactions between adsorbed molecules and paper substrate, over a wide range of partial pressures. A two-dimensional virial equation of state was employed to evaluate the extent of interactions by the compressibility factor (Z). Data of H-bonded molecules (water and butan-l-ol) and of more weakly interacting ones (ndecane and dioxane) were selected from the literature. At low surface coverage, the compressibility factor Z exceeds 1, showing a deviation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The reasons for this destruction are not fully understood yet. It is believed that main degradation mechanism of paper degradation is following: inks prepared with different ingredients causes both acidic hydrolysis and catalyzed oxidation of cellulose [1][2][3][4][5]. The desire to conserve the paper necessitates the development of effective treatments methods, which can only be possible after determination of the chemical composition of inks [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this destruction are not fully understood yet. It is believed that main degradation mechanism of paper degradation is following: inks prepared with different ingredients causes both acidic hydrolysis and catalyzed oxidation of cellulose [1][2][3][4][5]. The desire to conserve the paper necessitates the development of effective treatments methods, which can only be possible after determination of the chemical composition of inks [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…One side of these channels is formed by IPM, whereas another, by polysaccharide cellulose chains with cation-exchange groups fixed on these chains. It is known that the differential heat of adsorption of water on Whatman paper is higher than that of n -heptane, which is determined by specific interactions . If free fatty acids were added into the impregnating liquid, H + ions are able to move simultaneously both carried by fatty acid anions in the oil and through the aqueous channels as free ions from one carboxylic group fixed on a polymer to another. , Interactions of these two mechanisms lead to the changes of a lag time before transport reaches the steady state…”
Section: Discussionmentioning
confidence: 99%
“…Differential scanning calorimetry demonstrated that the freezing temperature of water in nitrocellulose-based membranes is below 0°C and depends on the pore size in a filter (0.05–0.45 μ) [ 62 ]. Note that heat of water adsorption on Whatman paper due to specific interactions is 114 KJ / mol , and it is much higher than that of medium-sized hydrocarbons [ 63 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ordering of impregnating oils is distorted by nitrocellulose polymer chains penetrating through the membrane. These polymers (not only proteins but also polysaccharides) carry ion-exchange groups and interact with water [ 63 , 65 ], thus forming ion-selective aqueous channels with a thickness of a few nm. Polysaccharides are a common component of biological membranes, especially those of plant cells, including wood.…”
Section: Introductionmentioning
confidence: 99%